The Generation Effect: Cavity Accessibility in Dense‐Shell Polyphenylene Dendrimers. Issue 1 (18th November 2014) - Brutschy, Malte; Stangenberg, René; Beer, Cornelia; Lubczyk, Daniel; Baumgarten, Martin; Müllen, Klaus; Waldvogel, Siegfried R.
Abstract: Size exclusion is a widespread phenomenon in supra‐ and macromolecular chemistry. Herein, the size exclusion properties of polyphenylene dendrimers on the surface of high fundamental frequency quartz crystal microbalances are reported. For this purpose, a new dense fifth‐generation polyphenylene dendrimer, which was previously not possible owing to the high steric demand of the dendron arms, was synthesized. By increasing the volume and size of subjected analytes an affinity shift from smaller to larger dendrimers can be obtained. Abstract : It's all relative : The confined geometry of polyphenylene dendrimers leads to a clear generation effect because the size and access to the voids in these dendrimers is determined by their generation. Host–guest behavior to benzene, toluene, and xylenes (BTX) analytes was investigated by using quartz crystal microbalances.